2003
DOI: 10.1074/jbc.m212324200
|View full text |Cite
|
Sign up to set email alerts
|

Isochorismate Synthase (PchA), the First and Rate-limiting Enzyme in Salicylate Biosynthesis of Pseudomonas aeruginosa

Abstract: In Pseudomonas aeruginosa the extracellular metabolite and siderophore pyochelin is synthesized from two major precursors, chorismate and L-cysteine via salicylate as an intermediate. The regulatory role of isochorismate synthase, the first enzyme in the pyochelin biosynthetic pathway, was studied. This enzyme is encoded by pchA, the last gene in the pchDCBA operon. The PchA protein was purified to apparent electrophoretic homogeneity from a PchA-overexpressing P. aeruginosa strain. The native enzyme was a 52-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
103
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 42 publications
1
103
0
Order By: Relevance
“…This is likely due to the fact that under the experimental conditions used, gene expression is not the only parameter which determines the amount of product formed. Indeed, we have shown previously that pyochelin formation could be significantly increased when the growth medium was supplemented with cysteine (Gaille et al, 2003), indicating that the intracellular cysteine pool is another important factor.…”
Section: Strainmentioning
confidence: 99%
“…This is likely due to the fact that under the experimental conditions used, gene expression is not the only parameter which determines the amount of product formed. Indeed, we have shown previously that pyochelin formation could be significantly increased when the growth medium was supplemented with cysteine (Gaille et al, 2003), indicating that the intracellular cysteine pool is another important factor.…”
Section: Strainmentioning
confidence: 99%
“…SDS-PAGE performed on eluted fractions indicated that the ICS monomer (estimated to be ϳ59 kDa, supplemental data) was exclusively enriched in the fractions with ICS activity. Therefore, similar to the bacterial ICS proteins Pae PchA (48) and Eco EntC (4), AtICS1 appears to function as a monomer, whereas the SAS Yec Irp9 appears to function as a dimer (9).…”
Section: Atics1mentioning
confidence: 99%
“…Reactions containing no added metal ion were also included. IPL activity is reported to be unaffected by divalent cations (48). However, lactic dehydrogenase (Sigma L-1254, rabbit muscle) activity may be inhibited by heavy metals such as Hg 2ϩ and Pb 2ϩ (Sigma-Aldrich Technical Service).…”
Section: Effect Of Other Metals On Ics Activitymentioning
confidence: 99%
See 2 more Smart Citations